ANALISIS KONTRIBUSI PAJAK DAERAH ATAS PENDAPATAN ASLI DAERAH KOTA BEKASI (Media Riset Akuntansi, 2022)
Currently the Bekasi City Revenue Agency is actively making every effort so that the regional tax target in the Bekasi City Revenue can be realized as a whole. This study aims to determine the contribution, obstacles that occur in the collection, the level of effectiveness of local taxes and the determination of the target of original revenue Bekasi City in 2015-2017. Data collection was carried out primary and secondary by taking data from the Bekasi City Revenue Agency and conducting interviews with the Head of Department. Testing is done by means of descriptive analysis including contribution analysis, analysis of effectiveness and analysis of the determination of the target of Local Original Revenue. The results of this study indicate that the level of local tax contribution is very good because the amount exceeds 50%, obstacles in conducting party collection still always occur both in terms of members of the Regional Revenue Agency and from the community itself, the level of effectiveness for each tax sector can be said to be very effective because many have reached 100%. The Bekasi City Regional Tax consists of, Restaurant Tax, Hotel Tax, Entertainment Tax, Street Lighting Tax and Advertising Tax.